2016
DOI: 10.1021/acs.est.6b03233
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Exhibits Pharmacological Effects and Trait-Based Sensitivity in a Marine Worm

Abstract: Global production of pharmacologically active compounds exceeds 100 000 tons annually, a proportion of which enters aquatic environments through patient use, improper medicine disposal, and production. These compounds are designed to have mode-of-action (MoA) effects on specific biological pathways, with potential to impact nontarget species. Here, we used MoA and trait-based approaches to quantify uptake and biological effects of fluoxetine, a selective serotonin reuptake inhibitor, in filter and deposit feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The difference between laboratory and field estimations of accumulation could be attributed to dietary assimilation and other environmental/ecological factors such as feeding strategy, habitat choice, water chemistry and bioavailability ( Vignati et al., 2007 ; Hird et al., 2016 ). As in vivo tests do not often include dietary exposure, it has been suggested that this may underestimate the accumulative potential of a compound ( Lagesson et al., 2016 ).…”
Section: Field Versus Laboratory Accumulation Of Pharmaceuticalsmentioning
confidence: 99%
“…The difference between laboratory and field estimations of accumulation could be attributed to dietary assimilation and other environmental/ecological factors such as feeding strategy, habitat choice, water chemistry and bioavailability ( Vignati et al., 2007 ; Hird et al., 2016 ). As in vivo tests do not often include dietary exposure, it has been suggested that this may underestimate the accumulative potential of a compound ( Lagesson et al., 2016 ).…”
Section: Field Versus Laboratory Accumulation Of Pharmaceuticalsmentioning
confidence: 99%
“…What is particularly starting to interest scientists is that these antidepressants can cause disruption to the normal functioning of aquatic life in laboratory experiments at low concentrations. The uptake of these compounds appears to be highly dependent on the organism's mode of feeding 9 . In terms of presence in the environment, for example, diazepam has been found in all matrices – wastewater, surface, ground and drinking water, soils, bio-solids and tissues 10 – and in concentrations as high as 10 ng/L in rivers and potable water 11…”
Section: Pharmaceuticals As Emergent Pollutantsmentioning
confidence: 99%